2021
DOI: 10.1111/jocs.15535
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic classification of mitral annular calcification for surgical and transcatheter mitral valve replacement

Abstract: Background and Aim of the Study: A systematic approach to quantify mitral annular calcification (MAC) in all-comers by multidetector computed tomography (MDCT) is essential to guide treatment, but lacking.Methods: From September 2015 to July 2019, 82 patients with MAC underwent MDCT at two institutions to evaluate for surgical mitral valve replacement (SMVR), transcatheter mitral valve replacement (TMVR), or medical management. Type 1 MAC was defined as <270°annular calcium and Type 2 as ≥270°. Absence/presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Heart team‐based algorithmic approaches to determine the management of mitral valve dysfunction in the setting of MAC are greatly needed. Following that line, the study by Alexis et al 12 is an important addition to the MAC literature. A key point from this paper is that developing a MAC treatment algorithm is challenging but achievable.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Heart team‐based algorithmic approaches to determine the management of mitral valve dysfunction in the setting of MAC are greatly needed. Following that line, the study by Alexis et al 12 is an important addition to the MAC literature. A key point from this paper is that developing a MAC treatment algorithm is challenging but achievable.…”
mentioning
confidence: 96%
“…In this issue of Journal of Cardiac Surgery , Alexis et al 12 proposed a MAC algorithm that attempts to shed more light on the systematic approach to determine the anatomic feasibility of patients with MAC requiring SMVR, TMVR, or a hybrid procedure. All patients underwent MDCT imaging to obtain standard anatomic measurements and MAC analysis.…”
mentioning
confidence: 99%
“…The use of multidetector computed tomography in addition to the analysis of the cardiac images using commercially available software, allowing one to simulate the valve position, have provided essential details during the preoperative planning. Using multidetector computed tomography analysis, Alexis and colleagues 3 recently reported an interesting MAC classification according to the extension of annular calcification and furthermore observed that a simulated reduction of neo-LVOT area ≤170 mm 2 , thickness of left ventricular septal, the aortomitral angle measurement, and the annular eccentricity with a cut-off ≥30%, may strongly predict early surgical failure.…”
mentioning
confidence: 99%
“…We congratulate Alexis et al 1 and the structural heart teams from Mount Sinai and Columbia for this series of high‐risk patients with mitral annular calcification (MAC) undergoing mitral intervention and for their novel classification of MAC based on treatment algorithm. Surgically, the presence of MAC is associated with risk of valve replacement over repair 2 and risk of ventricular rupture, myocardial infarction, and atrioventricular dissociation 3 .…”
mentioning
confidence: 99%
“…Alexis et al 1 propose a simple and potentially powerful conceptual model of mitral intervention based on MAC and risk of LVOTO. As the growth of transcatheter mitral interventions continues particularly for elderly patients, we are appreciating the growing importance of MAC both for technical success but also as a harbinger for poor overall prognosis.…”
mentioning
confidence: 99%